VARIATION IN HOPANOID COMPOSITION AND ABUNDANCE IN FOREST SOILS DURING LITTER DECOMPOSITION AND HUMIFICATION - Winkler A.; Haumaier L.; Zech W. (My University, 2001)
The structures and concentrations of hopanoids, a family of pentacyclic triterpenoids, were analysed to determine their contribution to the alkyl carbon with increasing soil depth of a Haplic Podzol (from the Oi to the Bs horizon). After the isolation of solvent-extractable hopanoids, the soil samples were subjected to sequential chemical degradation comprising the cleavage of ester and ether bonds and the oxidative cleavage of aliphatic-aromatic carbon linkages between hopanoids and the macromolecular organic matrix. Identification and quantification of the substances investigated were carried out by GC-MS. On the basis of the different analytical steps hopanoids were released as hydrocarbons, alcohols, and acids, with 31 up to 35 carbon atoms. No hopanoids were found in the Oi horizon; the concentrations rose markedly from the Oe to the Oa and E1 horizon (up to 565 μg g-1 total organic carbon) showing a minimum in the E2 horizon and a second maximum in the Bs horizon. The behaviour of these substances with increasing depth can be explained by varying activity of hopanoid-producing microorganisms and/or translocation processes due to podzolization. Because of the low concentrations, hopanoids and other triterpenoids do not play an important role in the enrichment of alkyl-carbon compounds during litter decomposition and humification in the forest soil under study.
Keywords: ALKYL CARBON; FOREST SOIL PROFILES; HOPANOIDS; CHEMICAL DEGRADATION; TETRACYCLIC TRITERPENOIDS